Right of a child to maintenance: harmonising the laws in Malaysia - Abdul Hak, Nora; Che Soh @ Yusoff, Roslina; Md Hashim, Noraini (2009)
One of the issues in child’s maintenance is the maximum age of a child in which a father is still responsible over the maintenance. Under the Civil law, there is no provision which requires the parent to provide maintenance if the child is pursuing his/her tertiary education. The Islamic Family law provides eighteen years old as the maximum age for a child to still be entitled to maintenance. It is also provided that if the child is pursuing his/her tertiary education, claim for the educational expenses can be made at the Shariah court against the parent. There is no similar provision under the Law Reform Act, 19676. There are also other aspects in child’s maintenance that can be harmonised under the existing laws in Malaysia. Thus, the paper will deliberate the right of a child to maintenance in Shariah and Civil law. Relevant legal provisions as provided for under the Malaysian laws i.e., the Law Reform Act, 1976 and the Islamic Family Law Act/Enactment and the practice of the Malaysian courts deliberating this right of a child will be the focus of the paper. Cases decided at the Shariah and Civil Courts relating to the claim of child’s maintenance will be analysed to study the practice of it in Malaysia as well as its problems and restrictions. It is hoped that by analysing the current the legal provisions on child’s maintenance and its practice in Malaysia, suggestions and recommendations can be made to further improve this area of law. Hence, the right of a child to maintenance as provided for under the law will be safeguarded.